Minasse Tcheraz’s Contacts of Europe and His Impressions of Berlin Congress - Serdar; Sakin (Gazi Akademik Bakış)
Before Berlin Congress assembled, Armenian Patriarch Nerses Varjabedyan had sent a delegation to the Congress in order to present the countries participating in the Congress with a memorandum that contained the requests of Armenian people and to secure these countries’ support throughout the Congress. The delegation, which was sent unknown to the Ottoman Empire, consisted of three members, i.e. former Patriarch Migirdic Kirimyan and Khoren Narbey as representatives, and Minasse Tcheraz as clerk and translator. The delegation left Istanbul on 8 March, 1878, and situations and experiences they had during the aforementioned journey to Europe was written by Minasse Tcheraz. He stated that they made contacts in Italy, Rome, London and Berlin, respectively. In accordance with these contacts, he mentioned meeting with Foreign Minister Luigi Corti in Italy, and Lord Salisbury in London. By means of these meetings during the journey, it became apparent that Armenians were unknown to Europeans. Various meetings, dinner parties and situations encountered at schools they visited were given as examples to illustrate this fact. Moreover, reasons regarding Europeans’ limited information about Armenians were stated. It was also indicated that thanks to the journey of the Armenian delegation, Europeans would have more information about Armenians. Tcheraz eventually indicated that Article 61, which was accepted in Berlin Congress, would not cause any problems, instead provide benefits for Armenians, and also stated the required steps to be taken in unity so as to attain these benefits.